2022
DOI: 10.1007/s10792-022-02353-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on primary balloon dacryocystoplasty and probing success in congenital nasolacrimal duct obstruction

Abstract: Purpose: To compare the success rates of balloon dacryocystoplasty (BDP) and probing as a primary procedure in congenital nasolacrimal duct obstruction (CNLDO) and investigate the effect of age on both procedures.Methods: A total of 135 patients (171 eyes) with simple or incomplete complex CNLDO were included in this retrospective study; complete complex CNLDO cases were excluded. The success rates for primary BDP (118 eyes) and for probing (53 eyes) were compared as overall and among the age groups; Group 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, in recent studies, Dericioğlu et al reported a higher overall success rate of 81.1% for BDP in their study. They maintained that primary BDP had a high rate of efficacy between 24 and 36 months, but that its success rate declined after 36 months ( 35 ). In our study, the lower success rate observed might be explained by the average age of patients undergoing BDP, which was 36±17 months with a median age of 31 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent studies, Dericioğlu et al reported a higher overall success rate of 81.1% for BDP in their study. They maintained that primary BDP had a high rate of efficacy between 24 and 36 months, but that its success rate declined after 36 months ( 35 ). In our study, the lower success rate observed might be explained by the average age of patients undergoing BDP, which was 36±17 months with a median age of 31 months.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon dacryocystoplasty is a minimally invasive procedure that can achieve lacrimal system patency and is usually performed mainly in cases of congenital nasolacrimal duct obstruction with failed probing [ 11 ]. It is known to be more effective than probing alone in older children after 18 months of age with congenital nasolacrimal duct obstruction [ 12 ]. It may also be used for the treatment of adult patients with partial nasolacrimal duct obstruction, especially in those who are poor candidates for dacryocystorhinostomy or general anesthesia [ 13 ].…”
mentioning
confidence: 99%